Efektivitas Polyurethane Foam sebagai Primary Dressing terhadap Fase Proliferasi Proses Penyembuhan Luka pada Pasien Venous Leg Ulcer di Wocare - Aji, Maskhul; Naziyah, Naziyah; Hidayat, Rizki (Universitas Malahayati, 2024)
ABSTRACT Venous Leg Ulcer is an open skin wound that occurs in areas affected by venous hypertension in the legs. In the proliferative phase, there is granulation tissue which is rich in new blood vessels that have been produced. Wound care has used Modern Dressings such as Polyurethane Foam which plays a role in absorbing exudate fluid and controlling hypergranulation, as well as putting pressure on the wound. To determine the effectiveness of Polyurethane Foam as Primary Dressing in the proliferation phase of the wound healing process in Venous Leg Ulcer patients in Wocare. Quasi-experimental research using a one group pre-test post test design. The total sample consists of 25 respondents. The sampling technique uses purposive sampling. The data was analyzed using the statistical test used was the paired sample t-test to determine the difference in pre-test and post-test scores using the Winner Scale assessment sheet. The research results mean the Winner Scale Pre-test score was 32.48 ± 6.319 and the post test is 20.72 ± 5.884. The research results showed that there was a difference between the Winner Scale scores before and after being given Polyurethane Foam with a p-value obtained of 0.000 (p<0.05). The use of Polyurethane Foam obtained effective results in reducing hypergranulation in the proliferation phase of Venous Leg Ulcer patients. with the results showing a p-value of 0.000 (p<0.05). For wound sufferers in Venous Leg Ulcer patients, it is hoped that they can use Polyurethane Foam Primary Dressing as an effort to speed up the wound healing process in the proliferation phase in VLU patients. Keywords: Venous Leg Ulcer, Polyurethane Foam, Proliferation Phase, Winner Scale ABSTRAK Venous Leg Ulcer adalah luka kulit terbuka yang terjadi di area yang terkena hipertensi vena di kaki. Fase proliferasi, terdapat jaringan granulasi yang memiliki kaya akan pembuluh darah baru yang telah dihasilkan. Perawatan luka telah menggunakan Modern Dressing seperti Polyurethane Foam yang berperan dalam menyerap cairan eksudat dan mengontrol hipergranulasi, serta memberi tekanan pada luka. Mengetahui Efektivitas Polyurethane Foam sebagai Primary Dressing terhadap fase proliferasi proses penyembuhan luka pada pasien Venous Leg Ulcer di Wocare. Penelitian quasi-eksperimen menggunakan rancangan one grup pre-test post test desain, Sampel total terdiri dari 25 responden. Teknik pengambilan sampel menggunakan purposive sampling. Data di analisis menggunakan uji statistik yang digunakan adalah uji paired sample t-test untuk mengetahui perbedaan skor pre test dan post test dengan menggunakan lembar pengkajian Winner Scale. Hasil penelitian rata-rata skor Winner Scale Pre-test sebesar 32,48 ± 6,319 dan post test sebesar 20,72 ± 5,884. Hasil penelitian menunjukan adanya perbedaan antara skor Winner Scale sebelum dan sesudah diberikan Polyurethane Foam dengan nilai p-value yang diperoleh sebesar 0,000 (p<0,05). Penggunaan Polyurethane Foam didapatkan hasil yang efektif dalam mengurangi hipergranulasi pada fase proliferasi pasien Venous Leg Ulcer. dengan hasil menunjukkan nilai p-value sebesar 0,000 (p<0,05). Untuk penderita luka pada pasien Venous Leg Ulcer diharapkan dapat menggunakan Polyurethane Foam Primary Dressing sebagai upaya mempercepat proses penyembuhan luka pada fase proliferasi pada pasien VLU. Kata Kunci: Venous Leg Ulcer, Polyurethane Foam, Fase Proliferasi, Winner Scale